Edukasi Resiko Penularan HIV/AIDS pada Ibu Rumah Tangga dan Lansia - Lingga Bullan; Widiyawati; Rika Permatasari; Siti Robiah Adawiah; Vina Novia Herdianti; Zakariya Adam; Silvia Yusantari (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Human immunity can be damaged by HIV (Human Immunodeficiency Virus), usually the virus is found in white blood cells in human body fluids. And AIDS is the presence of signs and symptoms due to the inability of the body's defense system. Objective: In the final process of counseling about the risk of transmitting HIV/AIDS to the elderly (elderly) and housewives, we hope that the people who are given education or counseling can understand about this disease so that they can expand their knowledge, especially among children/adolescents. Method: This counseling activity was carried out in collaboration between S1 Nursing students and the community of Margasari village, Limus hamlet, Sukajadi village, Sadananya sub-district which had several strategies, namely planning, implementation and evaluation. One of the planning activities is seen from the analysis of the number of people in the counseling. To housewives, the elderly, and the benchmark for the extent of public knowledge about the risk of disease transmission of HIV/AIDS. Result: The results of the research in Margasari village, Limus hamlet, Sukajadi village, Sadananya sub-district showed that housewives and the elderly did not understand about HIV/AIDS before counseling, after counseling the community could understand the risk of HIV/AIDS transmission. Conclussion: A conclusion was drawn based on the results of the counseling that the observators succeeded in providing education about the risk of HIV/AIDS transmission with success indicators in the form of questions and answers and questions from the audience could be answered by the observators. Extension activities are also well planned and implemented with indicators of material presentation, timeliness, and completeness.